2017
DOI: 10.1186/s12933-017-0546-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sitagliptin on the echocardiographic parameters of left ventricular diastolic function in patients with type 2 diabetes: a subgroup analysis of the PROLOGUE study

Abstract: BackgroundDiabetes is associated closely with an increased risk of cardiovascular events, including diastolic dysfunction and heart failure that leads to a shortening of life expectancy. It is therefore extremely valuable to evaluate the impact of antidiabetic agents on cardiac function. However, the influence of dipeptidyl peptidase 4 inhibitors on cardiac function is controversial and a major matter of clinical concern. We therefore evaluated the effect of sitagliptin on echocardiographic parameters of diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Previous research has shown LVM reduction though the administration of sulfonylureas [ 14 ], thiazolidines [ 15 ], or dipeptidyl peptidase 4(DPP4) blockers [ 16 ]. Nevertheless, some reports have also shown no significant LVM reduction upon the administration of OADs [ 17 19 ] and inconsistent effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown LVM reduction though the administration of sulfonylureas [ 14 ], thiazolidines [ 15 ], or dipeptidyl peptidase 4(DPP4) blockers [ 16 ]. Nevertheless, some reports have also shown no significant LVM reduction upon the administration of OADs [ 17 19 ] and inconsistent effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sitagliptin and liraglutide have been shown to improve diastolic function in the short term [11][12][13][14] and diabetes mortality increases with E/e′. 15 This may be the first report of differential effects of GLP-1 analogue and DPP-4 inhibitors on cardiac diastolic function with follow-up as long as 48 months.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, compared to placebo, improved left ventricular performance during dobutamine stress and reduced post‐ischaemic stunning were observed both acutely and after 1 month of sitagliptin, while alogliptin was associated with better coronary flow reserve and left ventricular systolic function compared to glimepiride after 3 months, despite similar reductions in HbA1c levels . In a 24‐week study in T2DM patients, the deterioration of diastolic dysfunction (E/e’, assessed using echocardiography) was attenuated by the addition of sitagliptin compared to conventional treatment alone, although glycaemic control and blood pressure were similar in both arms of the study, and neither cardiac structure nor systolic function were affected . Moreover, pooled safety analyses of the individual inhibitors and meta‐analyses of phase 3 clinical trials had also pointed towards a potential CV risk reduction with DPP‐4 inhibitors (eg, Reference ).…”
Section: What Has Been Learnt From Rcts?mentioning
confidence: 99%
“…In the case of the DPP-4 inhibitors, 3 of these trials have reported results; SAVOR-TIMI (saxagliptin 9 ), EXAMINE (alogliptin 10 ) and TECOS (sitagliptin 11 ), and 2 are on-going (CAROLINA 12 19 In a 24-week study in T2DM patients, the deterioration of diastolic dysfunction (E/e', assessed using echocardiography) was attenuated by the addition of sitagliptin compared to conventional treatment alone, although glycaemic control and blood pressure were similar in both arms of the study, and neither cardiac structure nor systolic function were affected. 20 Moreover, pooled safety analyses of the individual inhibitors [21][22][23][24][25] and meta-analyses of phase 3 clinical trials had also pointed towards a potential CV risk reduction with DPP-4 inhibitors (eg, Reference 14). Finally, an association between DPP-4 inhibitors and a reduction in surrogate markers of atherosclerotic CVD (carotid intima-media thickness, in some, [26][27][28] although not all 29 studies; aortic pulse wave velocity 30 ; arterial 18 F-fluorodeoxyglucose uptake 31 ) has been shown in smaller RCTs, again suggesting a possibility for a CV risk reduction.…”
mentioning
confidence: 99%